Analisis Komparatif Titik Impas (BEP) Penjualan Offline dan Online sebagai Dasar Penentuan Strategi Profitabilitas Pada PD. Sinar Mas Stationery ATK Bekasi - Yan Shen Kristianto; Eka Dyah Setyaningsih (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Sinar Mas Stationery ATK Bekasi is an MSME and a trading company (PD) engaged in the sale office stationery supplies, utilizing two sales channels, offline and online sales. Differences in cost structures and sales volumes across these channels result in varying risk and profit achievement, thus necessitating analysis as a basis for determining an appropriate profitability strategy. This study aims to analyze and compare the Break-Even point (BEP) between offline and online sales as a foundation for determining profitability strategies. The data collection methods used for this final project include documentation, interviews, and literature review, employing a quantitative non-statistical analytical approach. The data analysis at PD. Sinar Mas Stationery ATK Bekasi was conducted by classifying costs into fixed costs and variable costs for each sales channel. The next stage involved comparing the BEP values of offline and online sales to identify which channel provides a more optimal contribution to profit. By performing this comparative analysis, the store owner is expected to gain a solid basis for determining profitability strategies, enabling the optimization of profit margins and the minimization of operational risks.